المسؤولية العقدية لمتعهد الإيواء المعلوماتي: دراسة مقارنة - محسن، منصور حاتم; شعواط، عباس عبيد (جامعة بابل - كلية القانون, 2016)
The role played by the contractor shelter is a technical role purely that eventually the information on the network or the allocation of hard disk space for the contractor shelter and placed under the disposal of the user and enable it to benefit from this service and the duration of the technical means to achieve its optimal use of them, because the information and data that flow via the Internet until it reaches the user needs a combination of several efforts of people who, including contractor shelter, which is linked to the user's contract shelter informational, and the responsibility that arises here is the responsibility of nodal because they arising from breach of contract shelter agreement between the parties, and the lack of legal regulation regulates responsibility undertaker's shelter, so we came to address this issue by referring to the general rules contained in the Iraqi civil law and civil laws of comparison and settled eliminate it in these countries.
أن الدور الذي يقوم به متعهد الايواء يعد دور فني بحت يتمثل بتسكين المعلومات على شبكة الانترنت أو تخصيص مساحة من القرص الصلب لحاسبة متعهد الايواء ووضعها تحت تصرف المستخدم وتمكينه من الانتفاع من هذه الخدمة ومدة بالوسائل الفنية التي تحقق له الانتفاع الأمثل منها، لان المعلومات والبيانات التي تنساب عبر شبكة الانترنت حتى وصولها الى المستخدم تحتاج الى تضافر جهود عدة أشخاص والذي من ضمنهم متعهد الايواء ، الذي يرتبط بالمستخدم بعقد الايواء المعلوماتي ، وان المسؤولية التي تثار هنا هي مسؤولية عقدية لأنها ناشئة عن الإخلال بعقد الايواء المبرم بين الطرفين ، ولعدم وجود تنظيم قانوني ينظم مسؤولية متعهد الايواء ، لذا لجئنا لمعالجة هذا الموضوع من خلال الرجوع الى القواعد العامة الواردة في القانون المدني العراقي والقوانين المدنية محل المقارنة وما أستقر علية القضاء في هذه الدول.
Keywords: وسائل الإتصالات -- تكنولوجيا المعلومات -- المسؤولية العقدية -- الإيواء المعلوماتي -- الإنترنت -- النظام القانوني -- العراق -- المجتمع العراقي -- مستخلصات الأبحاث